Oil palm sap trunk as a medium culture / Luqmanul Hakim Abd Kahar, Ikmal Iskandar Kaszeman and M. Hafiz Mohd Zulpry - Abd Kahar, Luqmanul Hakim; Kaszeman, Ikmal Iskandar; Mohd Zulpry, M. Hafiz (Faculty of Plantation and Agrotechnology, 2023)
The oil palm also known as Elaeis guineensis, is such a productive plant, its oil is widely available and may be purchased at a cost that is not prohibitive. No other oil crop comes close to matching the productivity of palm oil when measured in terms of yield per hectare because with a potential production of 4 to 5 tonnes of crude palm oil per hectare per year, oil palm is the most. after 25 years of planting, the oil palm needs to be replanting. The oil palm must be cut down and the trunks were shredded into the pieces for nutrient recycling purpose. the trunk oil palm has the potential in growth medium because the pressed sap from oil palm trunks has strong potential as a feedstock for a microbial culture medium. Material use agar, shredded trunk and presser. For method to make the sample of OPT will be press in a laboratory with 80mPa pressure, becoming shredded and produce medium culture that based on oil palm sap it will fully utilize the palm oil trunk as oil palm sap produced from the process that press the oil palm trunk. Oil palm sap from oil palm trunk has high chance for being used in making growth medium. Oil palm sap contain a large volume of sugar and other valuable substances such as amino acids as well as organic acids. Oil palm trunk sap contain almost all macronutrient and micronutrient that needed for bacterial growth.